Fundamental of Entrepreneurship ENT300 : Fugen Industry Biodiesel Manufacturing Industry / Aaron Billy Tingga ... [et al.] - Tingga, Aaron Billy; Jasli, Jaynathan Lester; Edwin, Elsabba; Maizatul Akmam, Sauli; Saidi, Haldizam; Salvia, Darren (2014)
For this Fundamentals of Entrepreneurship (ENT300) course, our group has unanimously decided to establish Fugen Industry as our business project for this semester for this Fundamentals of Entrepreneurship course. The Fugen Industry are the business plan that derived from our group join effort that consists of six executives with Aaron Billy Tingga as the General Manager, Jaynathan Lester bin Jasli as the Administrative Manager Elsabba Edwin as the Marketing Manager l, Maizatul Akmam bin Sauli as the Marketing Manager 2, Haldizam bin Saidi as the Operating Manager, and Darren bin Salvia as the Financial Manager. Fugen Industry is an industry that manufacturing biodiesel, it is a substitute fuel that applicable for all diesel power engines. Diesel power engine main energy drive for all industry in this world. As it is the main drive for all transportation that is the cargo ship, all types of heavy truck, construction equipment and even our 4x4 vehicle and Includes the van and buses. Thus is due to the outstanding demand for diesel and its terrifying state of non-renewable energy as it's denve from fossil fuel that we chose to establish a business plan that manufacture its substitute that is the biodiesel. The biodiesel is a highly renewable energy as it can be derive from all form of vegetable and animal fats. It can also derive from used and unwanted oil and fats, such as used cooking and grease.